Hubungan antara Dukungan Sosial dengan Kualitas Hidup Penderita Hiv/Aids di Jawa Tengah - Permata, Fabila Sasa; Purnomo, Jusuf Tjahjo (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Quality of life is a person's personal view of their life. This view is shaped by the values and culture in their environment, as well as related to the individual's goals, expectations, standards, and concerns. Quality of life is a concept that involves physical and psychological aspects, social relationships, and interactions with the surrounding environment. One of the factors that influence quality of life is social support. This study aims to determine the relationship between social support and the quality of life of HIV/AIDS patients in Central Java. The research method used was quantitative with a correlational design. A total of 90 participants who were involved in this research process used purposive sampling. The instruments in this study used the World Health Organization Quality of Live HIV-BREF (WHOQOLHIV-BREF) (α = .940) and The Multidimensional Scale of Perceived Social Support (MSPSS) (α = .910). The results showed that there was a relationship between social support and the quality of life of HIV/AIDS in Central Java with r = 0.605 and α = 0.000 (p<0.05).